Sentidos da profissão docente - Cericato, Itale Luciane (2010)
This study aims to understand the senses and meanings attributed by teachers to their professional activity throughout their teaching experience. To this end, we interviewed three high school teachers working in the public educational system of São Paulo, each of them being in a different career time. The data were analyzed in the light of the postulates of the social-historical psychology, focusing on two central categories: meaning and significance. The findings indicated that the meanings attributed by each of the three teachers to their teaching activities are unique and singular, although sharing some common features. Among these representations, some are worth mentioning: a) the fact that teaching is defined by common sense ideas, which reproduce and, consequently, perpetuated a same discourse through generations of teachers. As a result, the necessarily knowledge constructed by the specialized literature about the teaching, and the teaching profession, is absolutely not considered; b) students are seen as unmotivated for learning; c) experience is perceived as more valuable for teaching than teaching formation or continuing education. All teachers pointed out that it is impossible to promote learning in all students, exposing, consequently, a lacks of political commitment with the role of Education. Furthermore, all teachers reported an absence of collaborative work within the school, confirming that the teaching activities are conducted primarily in isolation. Differently, the changes introduced in the recently implemented educational policies of São Paulo - such as the use of text books elaborated by the state or receiving credit for the school s results in students performance evaluation - are seen by each teacher in a particular way. The meanings attributed to the teaching activity itself are various: it is defined as the ability to transmit knowledge to a person devoid of it, or as the fulfillment of a goal that someone had always pursued, or yet as a daily and unfair struggle, given the stress involved in teaching. Based on these findings, the conclusion is that the teaching profession needs to be changed in several aspects, namely: the initial training, as it is currently defined, is not sufficient to provide future guidance in the profession, so that the offer of continuing education in a systematic way and within the schools themselves is imperative. Finally, it is extremely necessary to replace the culture of isolation by a collaborative one, allowing teachers to learn with their peers in exchanging their successful and painful experiences